Factors Associated with Occurrence of Campylobacteriosis on Village Chicken in Mataram - Anwar Rosyidi; Setyawan Budiharta; Doddi Yudhabuntara (Jurnal Sain Veteriner, 2012)
Campylobacter jejuni is responsible for about 90% of cases of campylobacteriosis in human with gastroenteritis. Efforts to prevent the incidence of campylobacteriosis in human should be started with anassessment on its level in poultry. This study aims to determine the factors associated with the presence of C. jejuni on village chicken in Mataram, Nusa Tenggara barat. Association between C. jejuni as the dependent variable with independent variables were analyzed using logistic regression. Prevalence of C. jejuni from a total of 216 samples in Mataram at chicken level was 35.6% and while at the farm level was 70.5% (31/44). Variables showed a positive association of C. jejuni occurrence in chicken consist of age of chicken more than 3 months, the number of chicken ownership, and cage with soil floor. While the variable showed a negative association to the incidence of C. jejuni was drinking water of chicken originated from wells. Model obtained using logistic regression in association with occurence of C. jejuni on village chicken in Mataram was Y = -2.033 + 0.271 (age of chicken more than 3 month) + 0.103 (number of chicken ownership) + 0.741 (cage with soil floor) - 0.890 (drinking water of chicken originated from wells)Keywords: Campylobacter jejuni, logistic regression, village chicken, drinking water, wells